Framework Administered Account for Selected Fund Activities : Africa Regional Technical Assistance Center South (AFRITAC South) Subaccount. (Policy Papers; Policy Paper ;, 2011)
In March 2009, the Fund established a new Framework Administered Account to administer external financial resources for selected Fund activities (the "SFA Instrument"). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of a subaccount within the SFA. This paper requests Executive Board approval to establish the Africa Regional Technical Assistance Center South (AFRITAC South) Subaccount (the "AFRITAC South Subaccount" or the "Subaccount") under the terms of the SFA Instrument.